Muatan Nilai-nilai Multikultural dan Antimultikultural dari Mimbar Masjid di Kota Solo - Zakiyuddin Baidhawy (Balai Penelitian dan Pengembangan Agama Semarang, 2014)
Abstract This research aims to identify the scope of religious sermons and materials in different mosques in Solo, and identify multicultural and anti-multicultral aspects presented in sermons. Using qualitative method and content analysis, the research found the following conclusions: First, the diversity of communities—ethnic, cultural, or religious— has received little attention from the preacher at various mosques and majelis taklim. Second, in addition to multicultural values, sermons and religious lectures contains some values of anti-multicultural, such as prejudice and stereotypes against other groups, particularly in relation to the non-Muslim and western countries. Third, the sermons material and religious lectures implied the intensity of purification. Along with the movement, religious preaching implied resistance to local culture (Java), which is considered as the main source of religious impurity. Finally, the development trend of Islam in Solo implies religious radicalization as reflected in hostility towards the local culture, foreigners and non-Muslims.Keywords: multiculturalism, antimulticulturalism, radicalism, mosque, religious speech AbstrakPenelitian ini bertujuan untuk mengidentifikasi lingkup materi khotbah agama dan khotbah di masjid-masjid dan majelis taklim di Solo, dan mengidentifikasi aspek-aspek multikultural dan anti-multikultural yang disampaikan dalam khotbah dan ceramah. Riset ini menggunakan metode penelitian kualitatif dan analisis isi. Studi ini menemukan kesimpulan sebagai berikut: Pertama, keragaman masyarakat—etnis, budaya, atau agama—mendapat sedikit perhatian dari pengkhotbah di berbagai masjid dan majelis taklim. Kedua, di samping nilai-nilai multikultural, khotbah dan ceramah keagamaan berisi beberapa nilai-nilai anti-multikultural, seperti prasangka dan stereotip terhadap kelompok lain, khususnya dalam hubungan dengan non-Muslim dan negara-negara barat. Ketiga, materi khotbah dan ceramah keagamaan tersirat intensitas gerakan pemurnian. Seiring dengan gerakan, berkhotbah keagamaan tersirat perlawanan terhadap budaya lokal (Jawa), yang dianggap sebagai sumber utama ketidakmurnian agama. Akhirnya, perkembangan Islam di Solo menyiratkan kecenderungan radikalisasi agama sebagaimana tercermin dalam sikap permusuhan terhadap budaya lokal, orang asing, dan non-Muslim.Kata kunci: multikulturalisme, anti-multikulturalisme, radikalisasi, masjid, ceramah keagamaan